Inside smart cities : place, politics and urban innovation - Karvonen, Andrew, 1971-; Cugurullo, Federico; Caprotti, Federico, 1980- (New York: Routledge, 2022)
"The era of the smart city has arrived. Only a decade ago, the promise of optimising urban services through the widespread application of information and communication technologies was largely a techno-Utopian fantasy. Today, smart urbanisation is occurring via urban projects, policies and visions in hundreds of cities around the globe. Inside Smart Cities provides real-world evidence on how local authorities, small and medium enterprises, corporations, utility providers and civil society groups are creating smart cities at the neighbourhood, city and regional scales. Twenty three empirically detailed case studies from the Global North and South (ranging from Cape Town, Stockholm and Abu Dhabi to Philadelphia, Hong Kong and Santiago) illustrate the multiple and diverse incarnations of smart urbanism. The contributors draw on ideas from urban studies, geography, urban planning, science and technology studies and innovation studies to go beyond the rhetoric of technological innovation and reveal the political, social and physical implications of digitalising the built environment. Collectively, the practices of smart urbanism raise fundamental questions about the sustainability, liveability and resilience of cities in the future. The findings are relevant to academics, students, practitioners and urban stakeholders who are questioning how urban innovation relates to politics and place"--Publisher's website.
Includes bibliographical references and index.
Keywords: Smart cities; City planning -- Technological innovations; Community development, Urban; Sustainable development; Smart cities; City planning -- Technological innovations; Community development, Urban; Sustainable development; Stadtplanung; Stadtentwicklung; Nachhaltigkeit